Engineering economy / William G Sullivan; Elin M Wicks; C Patrick Koelling - Sullivan, William G.
For courses in undergraduate introductory engineering economics. Understand the importance of engineering economics principles and how to make smart economic choices Used by engineering students worldwide, this bestselling text provides a sound understanding of the principles, basic concepts, and methodology of engineering economy. Explanations and examples that are student-centered and practical in real-life situations help students develop proficiency in the methods and processes for making rational decisions. Built upon the rich and time-tested teaching materials of earlier editions, the